Pengaruh Media ICT Berbasis Leaflet terhadap Tingkat Pengetahuan Wanita Usia Subur tentang Kista Ovarium - Savitri, Yulia; Fatmasari, Baiq Dika; Baiq Disnalia Siswari; Supiani (STIKes Hamzar, 2024)
Ovarian cysts are benign tumors in the form of abnormal sacs filled with fluid in the ovaries. The resulting impact will be disrupted resulting in fertility and difficulty getting pregnant, What is the level of WUS knowledge about ovarian cysts using leaflet-based ICTmedia in Batujai village. The study used quantitative research, pre-experimental methods and used a one-group pretest-posttestdesign with a population of 130 people, sampling technique using purposive random sampling, a total sample of 57 people. Theinstrument uses a questionnaire, data analysis uses a simple paired t test.The study found 57 respondents before counseling using ICT media based on leaflets, 36 people (63.16%) had less criteria, 3 people (5.26%) had good criteria. Then after counseling, theresults of good criteria were 41 people (71.93%), and less criteria were 2 people (3.51%). The statistical test used the SPSS application with the paired sample t test and obtained a P-Value of 0.000 <0.05. Then Ho is rejected and Ha is accepted. There is aninfluence of leaflet- based ICT media on the level of WUS knowledge about ovarian cysts in Batujai village